SPECTRUM OF SKIN DISORDERS PRESENTING TO KING ABDUL AZIZ HOSPITAL DURING HAJJ SEASON-2000 - Samdani, Azam Jah (Journal of Ayub Medical College Abbottabad, 2004)
Background: The pilgrimage (Hajj) to the holy mosque in the city of Makkah takes place once every year and during this huge gathering skin diseases are quite common due to hot weather and over crowding. The aim of this study was to collect and report data regarding different dermatological problems occurring during the holy month of Zil-hajj. Methods:Data regarding skin diseases was collected from pilgrims which were examined and diagnosed clinically at the Department of Dermatology King Abdul Aziz Hospital, during the month of Zil-Hajja of the year 2000. These patients were referred from various primary health centers, medical hajj missions of various countries and Children and Maternity hospital in Makkah. Results: During the month of Zil- hajja of the year 2000, 1510 cases were seen, of these 1143 were males and 367 were females. The criteria for diagnosis for most of the cases were mainly clinical. The highest number of patients was in the age group of 20-50 years. Eczemas of different types were the most common skin disease observed in these pilgrims, intertrigo was the next most common presenting condition this was followed by fungal and bacterial infections. Conclusion: A high frequency of skin diseases such as eczemas, intertrigo, pyoderma and fungal infections was found among the pilgrims. More detailed studies regarding skin conditions during this season would enable us to have better understanding of skin problems there management and prevention in full. Key Words: Overcrowding, Skin disorders, Eczemas, Intertrigo, Hajj.